Citrate utilization by Escherichia coli: plasmid- and chromosome-encoded systems. - Reynolds, C H (1983)
Citrate utilization plasmids have previously been identified in atypical Escherichia coli isolates. A different citrate-utilizing (Cit+) variant of E. coli K-12 arose as a consequence of two chromosomal mutations (B. G. Hall, J. Bacteriol. 151:269-273, 1982). The processes controlling the transport of citrate in both a Cit+ chromosomal mutant and a Cit+ plasmid system were studied. Both systems were found to be inducible in growth experiments. In transport assays with whole cells, citrate-grown cells accumulated [1,5-14C]citrate at two to three times the rate of uninduced cells. Only the Vmax was affected by induction, and the Km for whole cells remained at 67 microM citrate for the chromosomal strain and 120 microM citrate for the plasmid-conferred system. There was no detectable accumulation of radioactivity with [6-14C]citrate, because of rapid metabolism and the release of 14CO2. Energy-dependent citrate transport was found with membrane vesicles obtained from both the chromosome-conferred and the plasmid Cit+ systems. The vesicle systems were inhibited by valinomycin and carbonyl cyanide m-chloro-phenylhydrazone but not by nigericin and monensin. In contrast to whole cells, the vesicle systems were resistant to Hg2+ and showed identical kinetics with [1,5-14C]citrate and [6-14C]citrate. H+ appeared to be important for citrate transport in whole cells and membranes. Monovalent cations such as Na+ and K+, divalent cations such as Mg2+ and Mn2+, and anions such as PO4(3-), SO4(2-), and NO3- were not required. The two systems differed in inhibition by citrate analogs.